Characteristics of the Pro225His mutation in human immunodeficiency virus type 1 (HIV-1) reverse transcriptase that appears under selective pressure of dose-escalating quinoxaline treatment of HIV-1. - Pelemans, H; Esnouf, R; Dunkler, A; Parniak, M; Vandamme, A; Karlsson, A; De Clercq, E; Kleim, J; Balzarini, J (1997)
Treatment of human immunodeficiency virus type 1 (HIV-1)-infected CEM cell cultures with escalating concentrations of the quinoxaline S-2720 resulted in an ordered appearance of single and multiple mutant virus strains that gradually became resistant to the quinoxaline and other nonnucleoside reverse transcriptase (RT) inhibitors (NNRTIs). A novel mutation, Pro225His, consistently appeared in a Val106Ala RT-mutated genetic background. The contribution of this mutation to the resistance of the mutant HIV-1 RT to NNRTIs was additive to the resistance caused by the Val106Ala mutation. Interestingly, site-directed mutagenesis studies revealed that the Pro225His-mutated RT had acquired markedly greater sensitivity to bis(heteroaryl)piperazine (BHAP U-90152) (delavirdine) but not to any of the other NNRTIs. The kinetics of inhibition of the Pro225His mutant RT by the NNRTIs (including BHAP U-90152) was not substantially different from that observed for the wild-type RT. The hypersensitivity of the mutant enzyme and virus to BHAP U-90152 could be rationally explained by the molecular-structural determinants of the RT-BHAP complex, which has recently been resolved by X-ray crystallography.